A simple prediction method for the permeability coefficient of water-bearing sand layer after grouting compaction. Issue 1 (January 2021) - Chen, Jiale
Abstract: Due to the particularity of the pumping of the compound paste slurry material, the traditional stress analysis method is difficult to apply. Based on the cylindrical hole expansion model of compacted grouting, the theoretical formula of the compacted grouting displacement field of soil is established on the basis of simplified body strain. Based on the displacement field theory, the analytical solution of the soil permeability coefficient after grouting and compaction is established according to the compressed porosity and Konzeny-Carman equation. The field test of compact grouting was carried out, and the water injection test was used to obtain the change of permeability coefficient before and after grouting under different grouting intervals. The obtained results are in good agreement with the theoretical solution and have certain engineering guidance significance.